Case Peurunka : the essence of wellbeing - customer perspective - Ahtiainen, Annakaisa (2014)
Changes in the contemporary population structures have created a number of new opportunities for the wellbeing tourism industry worldwide. In Finland, one of the wellbeing tourism destinations going through these changes is the Spa Hotel and Rehabilitation Foundation Peurunka. Originally built in 1974 for the rehabilitation of the Finnish war veterans, Peurunka is nowadays developing its health and physical activity services to attract more recreational wellbeing tourists alongside the rehabilitees. In addition to the change of the clientele and as a result of more stressful and hectic lifestyles, individuals are more willing to invest in their wellbeing. This generates great potential for wellbeing operators to meet the growing demand by offering more extensive services and products to nurture holistic wellbeing.